Evaluation of Calf Muscular Function During the Recovery Phase After the Repair of an Achilles Tendon Rupture - Chai, Jung-Hoon; Bae, Sang-Won (Frontiers in Surgery, 2019)
Background: During the recovery phase after the repair of an Achilles tendon rupture measuring calf muscular function is important for predicting prognosis. Tensiomyography (TMG) is a selective and non-invasive diagnostic method for skeletal muscular contractile properties based on the displacement of the muscle belly. Case Presentation: Tensiomyography gives information about maximal displacement of the muscle belly (Dm), delay time, contraction time (Tc), sustain time, and relaxation time. Using Tensiomyography we evaluated a patient that had Achilles tendon rupture surgery. Findings: In this study, the maximal displacement of the muscle belly changed significantly compared to other parameters. The maximal displacement of the muscle belly decreased after cast removal day and increased gradually during the early recovery phase and then slightly decreased again during the late recovery phase. Conclusions: These responses of the maximal displacement of muscle belly show a correlation of the recovery of muscular function.